2013
DOI: 10.1111/j.2047-2927.2013.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone replacement therapy can increase circulating endothelial progenitor cell number in men with late onset hypogonadism

Abstract: SUMMARYCirculating endothelial progenitor cells (EPCs) are bone marrow-derived cells required for endothelial repair. A low EPC number can be considered as an independent predictor of endothelial dysfunction and future cardiovascular events. Recent evidence shows that patients with hypogonadal symptoms without other confounding risk factors have a low number of circulating progenitor cells (PCs) and EPCs, thus highlighting the role of testosterone in the proliferation and differentiation of EPCs. Here, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 40 publications
1
14
0
2
Order By: Relevance
“…Moreover, PDE5 inhibitors play an indirect role in vascular regenerative therapy for ED by facilitating EPC release from bone marrow and through their transdifferentiation in the peripheral blood (Foresta et al ., ; La Vignera et al ., ). Furthermore, testosterone replacement therapy can increase the number of circulating EPCs and improve erectile function in hypogonadal men (Liao et al ., ). Mobilization of EPCs from bone marrow has also been considered as a possible mechanism in the chronic administration of melatonin for the prevention of ED in diabetic rats (Qiu et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, PDE5 inhibitors play an indirect role in vascular regenerative therapy for ED by facilitating EPC release from bone marrow and through their transdifferentiation in the peripheral blood (Foresta et al ., ; La Vignera et al ., ). Furthermore, testosterone replacement therapy can increase the number of circulating EPCs and improve erectile function in hypogonadal men (Liao et al ., ). Mobilization of EPCs from bone marrow has also been considered as a possible mechanism in the chronic administration of melatonin for the prevention of ED in diabetic rats (Qiu et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…LOH-related hypogonadal symptoms include decreased muscle mass and strength, decreased bone mass and osteoporosis, increased central body fat, decreased libido and sexual desire, forgetfulness, loss of memory, difficulty in concentration, insomnia and a decreased sense of well-being [7]. LOH may be associated with a significant deterioration in health-related quality of life (HRQOL) and many adversely affect the function of multiple organ systems.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, other study had investigated the effect of TRT on the number of circulating EPCs in hypogonadal patients, the results showed that post-TRT, T levels and EPC numbers had increased significantly compared with the baseline level in which T level had no significant association with the number of circulating EPCs (Liao et al, 2013) (Table 5). Using of CD131, VEGFR2 in the CD34 triple-positive cells by the dual expression may signify a true limitation of this study in which the number of EPCs calculated by this dual marker will be much less than the actual number.…”
Section: Discussionmentioning
confidence: 90%